Decomposing functional β‐diversity reveals that low functional β‐diversity is driven by low functional turnover in European fish assemblages. Issue 6 (7th January 2013) - Villéger, Sébastien; Grenouillet, Gaël; Brosse, Sébastien
Abstract Aim One of the main gaps in the assessment of biodiversity is the lack of a unified framework for measuring its taxonomic and functional facets and for unveiling the underlying patterns. Location Europe, 25 large river basins. Methods Here, we develop a decomposition of functional β‐diversity, i.e. the dissimilarity in functional composition between communities, into a functional turnover and a functional nestedness‐resultant component. Results We found that functional β‐diversity was lower than taxonomic β‐diversity. This difference was driven by a lower functional turnover compared with taxonomic turnover while the nestedness‐resultant component was similar for taxonomic and functional β‐diversity. Main conclusions Fish faunas with different species tend to share the same functional attributes. The framework presented in this paper will help to analyse biogeographical patterns as well as to measure the impact of human activities on the functional facets of biodiversity.